2005
DOI: 10.3758/bf03195333
|View full text |Cite
|
Sign up to set email alerts
|

Coherence of the irrelevant-sound effect: Individual profiles of short-term memory and susceptibility to task-irrelevant materials

Abstract: We examined individual and developmental differences in the disruptive effects of irrelevant sounds on serial recall of printed lists. In Experiment 1, we examined adults (N ϭ 205) receiving eight-item lists to be recalled. Although their susceptibility to disruption of recall by irrelevant sounds was only slightly related to memory span, regression analyses documented highly reliable individual differences in this susceptibility across speech and tone distractors, even with variance from span level removed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
44
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 29 publications
10
44
1
Order By: Relevance
“…This finding accords with previous studies that showed that high WMC can attenuate the power of sounds to capture attention ). The experiments reported here also found that WMC is unrelated to the changing-state effect, a finding that is consistent with those from previous research (Beaman, 2004;Elliott & Cowan, 2005). This pattern of results was the same whether spoken letters (Experiment 1) or tones (Experiment 2) constituted the sound sequences that produced the disruption of the serial recall task.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding accords with previous studies that showed that high WMC can attenuate the power of sounds to capture attention ). The experiments reported here also found that WMC is unrelated to the changing-state effect, a finding that is consistent with those from previous research (Beaman, 2004;Elliott & Cowan, 2005). This pattern of results was the same whether spoken letters (Experiment 1) or tones (Experiment 2) constituted the sound sequences that produced the disruption of the serial recall task.…”
Section: Discussionsupporting
confidence: 81%
“…However, several authors have tried and failed to find this relationship (Beaman, 2004;Elliott & Cowan, 2005; for an exception, see Elliott, Barrilleaux, & Cowan, 2006). On the other hand, if the changing-state effect is caused by interference between order processes, as is proposed by the interferenceby-process account (Macken et al, 1999), then individual differences in the capability to process order, rather than WMC, should predict disruption.…”
mentioning
confidence: 99%
“…The findings of Experiments 1 and 2 do not, however, support a modular view of working memory that distinguishes between memory for music and speech. These findings are more consistent with evidence of mechanisms common to different types of auditory traces; proposals include general auditory segmentation mechanisms (Bregman, 1990;Jones et al, 1995), retrieval-based features subject to similarity-based interference (Jones & Macken, 1993;Nairne, 1990), and individual differences in activated features from longterm memory (Cowan, Saults & Nugent, 1997;Elliott & Cowan, 2005). The latter explanation, in particular, is consistent with the fact that musical experience mediates the differential interference of suppression on visually presented music.…”
Section: Discussionsupporting
confidence: 77%
“…Experiment 3 was also designed to test the original hypothesis: that visual and auditory presentation of notes are differentially affected by suppression, in a within-participants comparison of presentation modalities. Presentation modality effects in Experiment 1 were evaluated between participants, as in Murray (1967Murray ( , 1968; although there were no group differences in musical expertise in Experiment 1, individual differences could, in principle, have influenced the presentation modality effects (Elliott & Cowan, 2005). Therefore, in contrast to Experiment 1, in which the participants were able to rehearse the visually presented music under natural conditions (in whatever manner they preferred), Experiment 3 forced the participants to translate the notation into an auditory form in order to succeed at the task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation